Organic coatings : science and technology - Wicks, Zeno W. (John Wiley and Sons, 1996)
What are coatings? Polymerization and film formation. Flow. Mechanical properties. Exterior durability. Adhesion. Corrosion protection by coatings. Latexes. Aminao resins. Binders based on isocyanates: polyurethanes. Epoxy and phenolic resins...